2019
DOI: 10.1002/hbm.24577
|View full text |Cite
|
Sign up to set email alerts
|

Different roles of frontal versus striatal atrophy in HIV‐associated neurocognitive disorders

Abstract: Gray matter (GM) atrophy is frequently detected in persons living with HIV, even in the era of combination antiretroviral therapy (cART), but the specificity of regions affected remains elusive. For instance, which regions are consistently affected in HIV? In addition, atrophy at which regions is frequently associated with neurocognitive impairment in HIV? Resolving these questions can potentially help to establish the possible neural profiles of HIV‐associated neurocognitive disorders (HAND) severity, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 92 publications
(172 reference statements)
4
30
0
Order By: Relevance
“…Other subcortical brain regions have also been implicated in selective vulnerability to HIV and associated NCI. Vulnerability of the neostriatum (caudate + putamen) to HIV-associated blood-brain barrier disruption and impaired function has been observed, especially in individuals with HIV-associated dementia and HIV-encephalitis (Berger and Arendt 2000;Chaganti et al 2019;Israel et al 2019;Lopez et al 1999;Melrose et al 2008;Meltzer et al 1998). Our study also implicates the globus pallidus, which, along with caudate and putamen, shows neuroinflammation (microglial activation) in PLWH despite a suppressive combination of antiretroviral therapy (Vera et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other subcortical brain regions have also been implicated in selective vulnerability to HIV and associated NCI. Vulnerability of the neostriatum (caudate + putamen) to HIV-associated blood-brain barrier disruption and impaired function has been observed, especially in individuals with HIV-associated dementia and HIV-encephalitis (Berger and Arendt 2000;Chaganti et al 2019;Israel et al 2019;Lopez et al 1999;Melrose et al 2008;Meltzer et al 1998). Our study also implicates the globus pallidus, which, along with caudate and putamen, shows neuroinflammation (microglial activation) in PLWH despite a suppressive combination of antiretroviral therapy (Vera et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging is a promising approach to assess brain morphometric and functional changes that shows broad application prospects in the diagnosis and management of PLWH and may have the potential to shed light on the pathogenesis of HAND ( Clifford and Ances, 2013 ; Saylor et al, 2016 ; Campbell et al, 2019 ). Previous structural MRI studies indicated that PLWH display widespread brain atrophy in the subcortical nucleus as well as the frontal, parietal, occipital, temporal, and cerebellar cortices and cortical thinning in the frontal and temporal lobes and cingulate cortex ( Wilson et al, 2015 ; Underwood et al, 2017 ; Sanford et al, 2018a , b ; Israel et al, 2019 ; Hassanzadeh-Behbahani et al, 2020 ). Diffuse abnormalities in white matter (WM) microstructure were also noticed, including reduced fractional anisotropy with increased mean and radial diffusivity ( O’Connor et al, 2017 ; Underwood et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between cognitive performance and neuroimaging is controversial. Whereas neuroimaging alterations in morphometry, diffusion, FC, and network topology were reported to be correlated with cognitive function ( Wilson et al, 2015 ; Underwood et al, 2017 ; Haddow et al, 2019 ; Israel et al, 2019 ; Kato et al, 2020 ), there are also studies that failed to find any such associations ( Thomas et al, 2013 ; Su et al, 2016 ; Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…ERβ, however, is involved in mediating estradiol signaling in the immune and central nervous systems (for review, Paterni et al 2014). Within the central nervous system, cells containing ERβ mRNA or immunoactivity are widely dispersed (e.g., Li et al 1997;Shughrue et al 1997;Zhang et al 2002;Gonzalez et al 2007), and observed in brain regions (e.g., prefrontal cortex, ventral tegmental area, hippocampus) commonly associated with HAND (e.g., Maki et al 2009;Israel et al 2019).…”
Section: Introductionmentioning
confidence: 99%